Phytosterols reverse antiretroviral-induced hearing loss, with potential implications for cochlear aging - Sodero, Alejandro O. (2023)
Fil: Sodero, Alejandro O. Pontificia Universidad Católica Argentina. Facultad de Ciencias Médicas. Instituto de Investigaciones Biomédicas; Argentina,